(untitled) (Journal of Asian Geography, 2022)
Urban rail transit systems such as mass rapid transit (MRT) and light rail transit (LRT) are important components of urban transport networks. Investments in these infrastructures can improve accessibility for users of the urban transport network, and previous studies have shown that proximity to rail stations has a positive impact on property prices. However, these studies generally deal with developed Western countries, and there is limited research of this sort on developing countries, particularly Malaysia. Using a hedonic pricing model, this study therefore, estimates the impact of proximity to the new SBK MRT line on residential property prices in Greater Kuala Lumpur, Malaysia. To draw meaningful conclusions regarding the positive and negative impacts of the MRT on residential property prices, temporal and spatial dimensions were considered. Thus, both longitudinal and cross–sectional effects were estimated in a single model. This innovative approach allows us to compare changes in property prices before and after the MRT line became operational. The multi–band catchment areas of 0–0.4 km (the treatment zone) and 0.85–1.5 km (the control zone) from the nearest station were used. The results presented in this study indicate that a typical condominium/service residence unit located within 0.4 km (the treatment zone) from the nearest MRT station and transacted after the system was operational on the northwest side of the city could earn a premium of approximately 9.5%, or RM 99,874 of the city’s mean home price, while a typical similar property located within the same distance from the nearest MRT station but transacted before (during construction, to be precise) the system was operational could generate a premium of about 6%, or RM 63,078 of the city’s mean home price, compared to those outside of this distance. Findings from this study have significance for the potential implementation of land value capture policy as an alternative source of revenue to fund or partially fund urban rail transport in Greater Kuala Lumpur, which is totally neglected.